Changing Values Through Generations - Špindler, Tomi (Academica turistica, 2022)
Mountain tourism is becoming an increasingly important part of tourism in the Alpine countries, so research among mountain tourists is necessary. The changing values of different generations of tourists play a major role in their behaviour in a high-altitude environment and consequently affect the condition of these areas. Therefore, the purpose of this study is to determine the values of different generations of mountain tourists, different genders of tourists and among members and non-members of mountaineering associations. To achieve this purpose, a quantitative approach was used. The data was collected through a self-completion questionnaire in physical form at locations of 1st category mountain huts in Slovenian mountains during the 2020 summer mountaineering season. As part of the research, the sample was divided into four groups according to the year of birth of participants. With multivariate analysis, the existence of significant differences between groups of respondents of different ages, gender and membership, according to their values, was determined. The results of the research demonstrate the correlation between prevailing mountaineering values of mountain tourists and their characteristics. The research helps us to understand the mountaineering values of tourists who visit the mountains and fills the knowledge gap in the field of the differences between the values of different generations of mountain tourists, different genders and among membership in mountaineering associations. As outdoor activities are also gaining in popularity during the Covid-19 pandemic, the results of this research can be useful for attracting new members to mountaineering organizations, preserving mountaineering culture and sustainable development of tourism in the mountains.
Keywords: generacije; generations; gorski turizem; mountain tourism; values; vrednote